2017
DOI: 10.3389/fmicb.2017.00296
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stress Factors Related to Cheese-Making Process and to STEC Detection Procedure on the Induction of Stx Phages from STEC O26:H11

Abstract: Shiga toxin-producing Escherichia coli (STEC) are responsible for human infections, ranging from mild watery diarrhea to hemorrhagic colitis (CH) that may be complicated by hemolytic uremic syndrome (HUS). The main STEC virulence factor is Shiga toxin encoded by the stx gene, located in the genome of a bacteriophage integrated into the bacterial chromosome. The serotype O26:H11 is the second HUS-causing serotype worldwide (after O157:H7), and the first found in dairy products such as raw-milk cheeses. A small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…It is difficult to have a general overview of STEC contamination in cheese because measurement methods have varied from one country to another. Worldwide, serotype O26:H11 is second only to E. coli O157:H7 for causing HUS (Hemolytic Uremic Syndrome), and is the one most often found in dairy products such as raw-milk cheeses (Bonanno, Delubac, Michel, & Auvray, 2017). Miszczycha et al (2014) showed that E. coli O26:H11 grew better and was more persistent than E. coli O157:H7 in various experimentally contaminated raw-milk cheeses.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to have a general overview of STEC contamination in cheese because measurement methods have varied from one country to another. Worldwide, serotype O26:H11 is second only to E. coli O157:H7 for causing HUS (Hemolytic Uremic Syndrome), and is the one most often found in dairy products such as raw-milk cheeses (Bonanno, Delubac, Michel, & Auvray, 2017). Miszczycha et al (2014) showed that E. coli O26:H11 grew better and was more persistent than E. coli O157:H7 in various experimentally contaminated raw-milk cheeses.…”
Section: Introductionmentioning
confidence: 99%
“…While the most likely reason for non-isolation is the background microbiota, this may also be as a result of free stx -containing phage. Recent studies suggest that the cheesemaking process triggers the production of stx containing prophages, potentially interfering with the analysis of STEC in the finished products [33]. These studies demonstrated that oxidative (aeration and exposure to oxygen) and salt stress, which are both likely to occur during cheesemaking, had the ability to induce stx phages in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that an increase in temperature can also induce phages when associated with other inducers. 17 Antibiotic treatment of STEC is still a matter of debate, although azithromycin appears to be the most effective agent. 18 Azithromycin is thought to be able to inhibit Stx-stimulated cytokine production by human peripheral blood mononuclear cells and monocytes.…”
Section: Discussionmentioning
confidence: 99%